NS5A replication complex inhibitor daclatasvir in the basis of chronic hepatitis C interferon-free therapy - M. V. Mayevskaya; M. S. Zharkova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze antiviral activity of a new NS5A replication complex inhibitor daclatasvir in patients with chronic HCV-infection in relation to different genotypes, including patients with failure of previous antiviral therapy, with liver cirrhosis, within different modes of treatment.Summary. Daclatasvir is NS5A inhibitor which has proven high antiviral activity in relation to all hepatitis C virus genotypes. Prescription of the drug in combination to pegilated interferon and ribavirin for treatment-naive patients made possible to reduce treatment duration from 48 to 24 weeks and to increase frequency of sustained virologic response (SVR) to 87% in 1b genotypeand to 100% — in 4-th genotype. Daclatasvir is no less effective within treatment modes that include other direct-acting antiviral agents as well. In combination to asunaprevir (second waveprotease inhibitor) it demonstrated high rate of SVR both in untreated patients (91%), and in «difficult to treat» groups patients — with liver cirrhosis and nonresponders to the previous therapy (up to 83%). Quadrotherapy including pegilated interferon, ribavirin and asunaprevir has allowed to increase treatment efficacy in nonresponders with 1b genotype even more (up to 98,9% of SVR). Combination of daclatasvir and sofosbuvir is considered to be effective as well, demonstrating 96% rate of SVR in patients with the 3-rd genotype without liver cirrhosis, irrespective of treatment experience. A safety profile and tolerability of daclatasvir is good, comparable to placebo group. The drug is not registered in Russia yet, its approval in combination to asunaprevir is expected soon.Conclusion. Clinical trials have demonstrated that combination of daclatasvir with other medications possessing direct antiviral action, in particular with asunaprevir, and with pegilated interferon and ribavirin significantly increases treatment response rate at different categories of patients with chronic HCV-infection; that allows to reduce treatment duration of these patientsgroups. The drug possesses favorable safety profile, including at treatment of liver cirrhosis.